ANALISIS PENERAPAN ANIMASI DALAM GAME - Tandeo, Ewaldo Jovial; Pramayasa, I Made Hendra Mahajaya (Pusat Penerbitan LPPM ISI Bali, 2025)
Video games and animation are two elements that are difficult to separate. Since the development of the video game industry, many games have been created using either two-dimensional or three- dimensional animation techniques. Animation certainly plays a crucial role in making games engaging. Generally, animation is more prominently used in video games of the RPG (Role-Playing Game) genre. It not only delights gamers with visually captivating graphics but also contributes to the storyline and character development. Therefore, various observations and analyses of animation and visuals in video games have been conducted. For example, examining the animation used in the games being observed. Various RPG video games utilize two-dimensional, three-dimensional, or a combination of both animations, providing gamers with a new experience through stunning graphics. Thus, the combination of animation and video games can entertain and inspire many people.